CellMemory: hierarchical interpretation of out-of-distribution cells using bottlenecked transformer - Wang, Qifei; Zhu, He; Hu, Yiwen; Chen, Yanjie; Wang, Yuwei; Li, Guochao; Li, Yun; Chen, Jinfeng; Zhang, Xuegong; Zou, James; Kellis, Manolis; Li, Yue; et al. (Genome Biology, 2025)
Machine learning methods, especially Transformer architectures, have been widely employed in single-cell omics studies. However, interpretability and accurate representation of out-of-distribution (OOD) cells remains challenging. Inspired by the global workspace theory in cognitive neuroscience, we introduce CellMemory, a bottlenecked Transformer with improved generalizability designed for the hierarchical interpretation of OOD cells. Without pre-training, CellMemory outperforms existing single-cell foundation models and accurately deciphers spatial transcriptomics at high resolution. Leveraging its robust representations, we further elucidate malignant cells and their founder cells across patients, providing reliable characterizations of the cellular changes caused by the disease.